Trimethylamine Gas Sensor Based on Electrospun In2O3 Nanowires with Different Grain Sizes for Fish Freshness Monitoring - Xiangrui Dong; Bo Zhang; Mengyao Shen; Qi Lu; Hao Shen; Yi Ni; Yuechen Liu; Haitao Song (Chemosensors, 2025)
Seafood, especially marine fish, is highly prone to spoilage during processing, transportation, and storage. It releases pungent trimethylamine (TMA) gas, which severely affects food quality and safety. Metal–oxide–semiconductor (MOS) gas sensors for TMA detection offer a rapid, convenient, and accurate method for assessing fish freshness. Indium oxide (In2O3) has shown potential as an effective sensing material for the detection of TMA. In this work, one-dimensional In2O3 nanowires with different grain sizes and levels of crystallinity were synthetized using the electrospinning technique and underwent different thermal calcination processes. Gas-sensing tests showed that the In2O3–3 °C/min–500 °C gas sensor exhibited an outstanding performance, including a high response (Ra/Rg = 47.0) to 100 ppm TMA, a short response time (6 s), a low limit of detection (LOD, 0.0392 ppm), and an excellent long-term stability. Furthermore, the sensor showed promising experimental results in monitoring the freshness of Larimichthys crocea (L. crocea). By analyzing the relationship between the grain size and crystallinity of the In2O3 samples, a mechanism for the enhanced gas-sensing performance was proposed. This work provides a novel strategy for designing and fabricating gas sensors for TMA detection and highlights their potential for broad applications in real-time fish freshness monitoring.